German Annual of Spatial Research and Policy 2009 New Disparities in Spatial Development in Europe - Kilper, Heiderose. (German Annual of Spatial Research and Policy, 2009)
The German Annual of Spatial Research and Policy 2009 explores the concept of spatial disparities, which has its roots in national spatial planning and spatial development policy, and discusses new spatial disparities in Europe. The scientific articles provide an overview of the process of formulating a European position on "territorial cohesion" and address some of the issues surrounding new spatial disparities at different levels in different European countries. This includes the transformation from the industrial to the knowledge society, the development of settlement structures, spatial patterns of suburbanisation processes, demographic transformation, and equal ecological living conditions in the European Union.